Bioactive compounds of rice (Oryza sativa L.): Review on paradigm and its potential benefit in human health. (March 2020) - Verma, Deepak Kumar; Srivastav, Prem Prakash
Abstract: Background: Knowledge of rice's nutritional value and health benefits is essential to increase rice consumption in people's daily diet. Rice is known as a queen of cereal crops that have a high nutritional value such as carbohydrate, fat, fiber, protein, vitamins as well as food energy, minerals profile and fatty acids. Scope and approach: The present review paper mainly focuses on the chemistry of rice bioactive compounds, methods of extraction, identification, and characterization as well as biological activities and health benefits. Key findings and conclusions: The nutritional components are found in various types of rice which grown and utilized by farmers and consumers respectively with more than 60% population worldwide. In addition to nutritional components, there are many phytochemicals present in rice have been identified as bioactive compounds which have their many high biological activities, in which antioxidant, anticancer, antidiabetic and antiinflammation activities are major one, as other cereals have and also exhibit their potential beneficial health effects in human as they all consume rice in their daily routine diet. Graphical abstract: Image 1 Highlights: Extracts of pigmented and non-pigmented rice contain various bioactive compounds (BACs). Solvent extraction is the most common conventional method used to extract BACs from rice. HPLC is the most frequently used analytical method to identify and characterize rice BACs. Biologically active phytochemicals in rice prevent many chronic human diseases. These BACs are creating new interests for industrial use in food and nutraceutical products.